ПАСТКА ДЛЯ ГЕТЬМАНИЧА: СУЧАВСЬКА КАМПАНІЯ Т. ХМЕЛЬНИЦЬКОГО (1653) - Chuchko, Mychailo (Чернівці, Чернівецький національний університет, 2023)
The article deals with the problems of difficult relations between the Moldavian prince Vasile Lupu and the Zaporozhzhia Army after the start of the War of Liberation in Ukraine under the leadership of Hetman B. Khmelnytskyi against Polish domination.
A TRAP FOR HETMANYCH: THE SUCEAVIAN CAMPAIGN OF T. KHMELNYTSKYI (1653)